Forecasts of seasonal to inter-annual beach change using a reduced physics beach profile model - Harshinie Karunarathna (Marine Geology, 2015)
Seasonal to inter-annual variability of beach profiles has been investigated using a one dimensional beach profile model developed on the ‘reduced-physics’ modelling approach. The model uses a diffusion formulation as the governing equation and adopts an inverse modelling technique for solving the equation. The model was applied to Hasaki Beach in Japan to investigate medium term beach change. Hasaki beach is longshore uniform and characterised by a highly dynamic longshore bar-trough system. Seasonal to inter-annual scale beach change was then forecasted using the model. The results are compared with beach change determined from measured beach profiles at Hasaki between 2007 and 2011. The simple modelling approach used yields encouraging results of seasonal to inter-annual scale beach change at Hasaki Coast.